Improvement of Stretchable and Washable Carbon-Nanotube-Based Textile Supercapacitors by using Molybdenum Trioxide Nanoflakes and Prewashing Treatment - Duy, Le Thai; Sial, Qadeer Akbar; Seo, Hyungtak (Advanced Materials Technologies, 2022)
The attraction of electronic textiles for next-generation wearable electronic devices has raised the demands of washable and stretchable energy storage. However, negative effects of washing on the textile-based devices are majorly known. In this work, besides the innovation of a conventional stretchable composite based on carbon nanotubes (CNT) and polydimethylsiloxane (PDMS) for textile-based supercapacitors, findings regarding negative and positive effects of washing are introduced. Since the CNT-and-PDMS-based composite (CNT+PDMS) owns high stretchability but low electrochemical performance, two strategies using molybdenum trioxide (MoO3) nanoflakes are designed for upgrading the composite performance. Through stretching, washing, and electrochemical tests, the pros and cons of these strategies are revealed and discussed. Besides, a positive effect of chemical treatment of a liquid detergent (i.e., prewashing) is discovered, and it can improve the prewashed supercapacitor electrodes from 10 to 84 mF cm−2 at a scan rate of 10 mV s−1. Compared to supercapacitor cells assembled from unwashed electrodes, those of the sufficiently prewashed electrodes possess similar stretchability (≈60%) but threefold higher energy and power densities (3.9 μWh cm−2 and 0.89 mW cm−2, respectively). Overall, those findings are beneficial for the development of sustainable e-textiles for wearable electronic applications.
Keywords: Chemical treatments; Effect of chemicals; Effect of washing; Electrochemical performance; Electrochemical test; Liquid detergents; Nano-flakes; Pre-washing; Supercapacitor electrodes; carbon nanotubes; molybdenum trioxide; stretchable; supercapacitors; textile; washable